Efficacy of vermicompost and biochar on the growth and yield of green cabbage (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
Organic production of Green Cabbage may ensure the nutritional status and food safety for the consumers, but maintaining the productivity and economic viability of inorganic production is almost impossible for farmers of Bangladesh. At this context, a study was carried out at the Horticulture farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from October 2017 to March 2018 to evaluate the efficacy of vermicompost and biochar on agronomic properties and economic of cabbage. Four biochar treatments, ( B0: 0 t ha-1 biochar, B1 :2 t ha-1 , B2 :6 t ha-1 and B3 :10 t ha-1) and three vermicompost treatments (Vc0 : 0 t ha-1, Vc1 :4 t ha-1 and Vc2 :8 t ha-1 ) were selected. B0Vc0 was considered as control. The results revealed that maximum highest plant height, number of leaves plant-1, leaf length, leaf breadth and plant spread were obtained when the B3 was mixed withVc2. But the thickness of head (10.29 cm), diameter of head (16.66 cm), % dry matter of cabbage (14.93%), weight of cabbage head plant-1 (1370 g) and yield of cabbage (52.75 t ha-1) were obtained from the treatment combination of B2Vc2. In terms of economic sustainability, the net return (Tk 523598) with highest BCR (3.70) was obtained from the treatment combination of B1Vc1.These results provide prove the effectiveness of biochar and vermicompost in sustainable Cabbage production. It also provides baseline guidelines for further investigation of choosing the appropriate combination of organic amendments based on crop requirement to maximize economic value.Asian Australas. J. Biosci. Biotechnol. 2021, 6 (2), 68-74